The Relationship Between Attachment Styles and Difficulty in Emotion Regulation: Investigating the Moderating Role of Reflective Functioning - Fatemeh Arab Alidoosti; Mahmoud Dehghani; Maryam Roshan; Somayeh Robat Milli (روانشناسی بالینی و شخصیت)
Introduction: While numerous studies have confirmed the relationship between attachment and emotional regulation, there has been limited focus on the mediating factors involved. The term  a new concept in psychoanalysis that refers to psychological processes grounded in mentalization. This concept shares common roots with these two constructs and has been examined in the present study. The aim of this study was to investigate the moderating role of reflective functioning in the relationship between attachment styles and difficulties in emotion regulation.Method: The design of this study is non-experimental and correlational. The participants included students from Payam Noor Universities in West Azerbaijan (Miandoab, Shahindej, Bukan, and Urmia) who were enrolled during the academic year 2018-2019. 180 individuals were selected using multi-stage cluster sampling, which involved three stages: the first stage was the university, the second stage was the faculty, and the third stage was the class. These participants completed the Reflective Functioning Questionnaires (RFQ), the Attachment Styles questionnaire (Hazen and Shaver, 1987), and the Difficulty in Emotion Regulation Scale (Gratz, 2004).Results: Hierarchical regression analysis indicated that individuals with a stronger secure attachment style exhibit greater confidence, which in turn facilitates easier emotion regulation. In addition, possessing an avoidant or anxious attachment style, coupled with high levels of uncertainty, complicates the process of emotion regulation.Discussion and Conclusion: The results of the present study indicate that the reflective function of certainty and uncertainty moderates the relationship between attachment styles and difficulties in emotion regulation. Specifically, secure attachment styles, along with the reflective function of certainty, are associated with reduced difficulties in emotion regulation, while insecure attachment styles and the reflective function of uncertainty are linked to increased difficulties in emotion regulation.